Characterization and phylogenetic analysis of the complete mitogenome of the Arctic skate Amblyraja hyperborea (Rajiformes; Rajidae) - Hong Keun Park; Moongeun Yoon; Keun-Yong Kim; Yun-Hwan Jung (Mitochondrial DNA. Part B. Resources, 2020)
The Arctic skate Amblyraja hyperborea is common in the cold water of the Atlantic and Pacific Arctic. Its distribution and taxonomy have been open to discussion. Here, we report on the whole mitochondrial genome sequence of A. hyperborea and the subsequent characterization. The mitogenome is 16,729 bp in length and consists of 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. The phylogenetic tree we reconstruct with the mitogenomes of related skates within the order Rajiformes supports the monophyletic assemblage congruent with recent studies, whilst raising the necessity of further investigations to elucidate the relationship among some rajid genera.